Analysis Of The Heavy Metal Content Of Hg, Pb AND Cu In Water, Sediment And Eceng Gondok (Eichornia crassipes) Plants In Lake Tondano - Sayow, Febrian; Polii, Bobby J. V.; Sinolungan, Meldi Tieneke Magdalena (Jurnal Agroekoteknologi Terapan, 2024)
This research aims to analyze the heavy metal content of Mercury (Hg), Lead (Pb), and Copper (Cu) in Water, Sediment, and Water Hyacinth Plants (Eichornia Crassipes) in Lake Tondano. Held at Lake Tondano. The method used is descriptive research and laboratory analysis. Sampling of water, sediment, and water hyacinth plants was carried out twice (in conditions of no rain (TH) and rain (H)), analysis of the heavy metal Mercury was carried out at the SGS WLN Manado Laboratory, and the heavy metals Lead and Copper at the Baristand Laboratory. The laboratory analysis method is the Atomic Absorption Spectrometry Method (SSA). Based on research results, the heavy metal content of Mercury (Hg), Lead (Pb), and Copper (Cu) has been detected in water, sediment, and water hyacinth plants (Eichornia Crassipes), however, the heavy metal content in water and sediment has not exceeded the quality standard limits. has been set. Keywords: Heavy Metals, Lake Tondano, Water, Sediment, Water Hyacinth Plants. Abstrak Penelitian ini bertujuan untuk menganalsis kandungan logam berat Merkuri (Hg), Timbal (Pb) dan Tembaga (Cu) pada Air, Sedimen dan Tanaman Eceng Gondok (Eichornia Crassipes) di Danau Tondano. Dilaksnakan di Danau Tondano. Metode yang digunakan adalah penelitian deskriptif dan analisis laboratorium. Pengambilan sampel air, sedimen dan tanaman eceng gondok dilakukan sebanyak 2 kali (pada kondisi tidak hujan (TH) dan hujan (H)), analisis logam berat Merkuri dilakukan di Laboratorium SGS WLN Manado dan logam berat Timbal dan Tembaga di Laboratorium Baristand. Metode analisis laboratoriumnya adalah Metode Spekrometri Serapan Atom (SSA). Berdasarkan hasil penelitian kandungan logam berat Merkuri (Hg), Timbal (Pb) dan Tembaga (Cu) sudah terdeteksi pada Air, Sedimen akan dan Tanaman Eceng gondok (Eichornia Crassipes) akan tetapi kandungan logam berat pada air dan sedimen belum melewati batas baku mutu yang sudah ditetapkan. Kata Kunci: Logam Berat, Danau Tondano, Air, Sedimen, Tanaman Eceng Gondok.